If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(26 + x) = 264 (26 * 2 + x * 2) = 264 (52 + 2x) = 264 Solving 52 + 2x = 264 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-52' to each side of the equation. 52 + -52 + 2x = 264 + -52 Combine like terms: 52 + -52 = 0 0 + 2x = 264 + -52 2x = 264 + -52 Combine like terms: 264 + -52 = 212 2x = 212 Divide each side by '2'. x = 106 Simplifying x = 106
| X(4x-2)+(3x-5)=(7x+9)(x-2) | | 4x^3+16x^2=16x | | 2[x+3(4-x)]=3x+1 | | -6m-m=-7 | | (W/-3v^4)^2 | | -8(2p-4)=-6p+22 | | 16x^2-25x^2=0 | | 0.75+y=2 | | 0.4(x+100)=0.47x-478 | | x^5-12=42-x^3 | | 3f^2-12f=0 | | -4+r+5r=-4 | | x^2-2sqrt(5)x+5=0 | | 80x^3=5x | | 5y+10=60-5y | | 52-(3x+16)=4x+15 | | -8x+15+5x=9 | | -28+2r=4(-5r-7) | | (4a^4/b^5)-3 | | 2y(y+16)=14 | | -(n^2-11n)/(14)=2 | | 3x+301-4x-33=108-16x-100 | | X+6.62=6.37 | | (X^2-4x)/6-(5x)/3=1 | | x^5-12=42 | | 3(x+2)+4=5x+y | | -6(1-6x)-4=-38+8 | | 5+9i^2= | | 2x+1=1212 | | 27x^4/y | | 9x+3=38+4x | | b+b+2b+(-3)*b= |